Assessment of β-human-derived chorionic gonadotrophic hormone (βhCG) and pregnancy-associated plasma protein A (PAPP-A) levels as predictive factors of preeclampsia in the first trimester among Iranian women: a cohort study - Maryam Honarjoo; Shahnaz Kohan; Elahe Zarean; Mohammad Javad Tarrahi (BMC, 2019)
Abstract Background Preeclampsia (PE) is a leading cause of maternal and perinatal mortality. There are controversial findings regarding the prediction of PE through the assessment of the Pregnancy-Associated Plasma Protein A (PAPP-A) and β-Human-Derived Chorionic Gonadotrophic hormone (βhCG) levels in the first trimester of pregnancy. Therefore, this cohort study was conducted to evaluate of PAPP-A and βhCG levels as predictive factors for PE development in the first trimester among Iranian women. Methods In this cohort study, a total of 4605 volunteer Primigravida and Multigravida women were selected by the census from 16 randomly selected Health Centers in Isfahan, Iran, from July 2016 to June 2018. Eligible pregnant women participated in the study had already undergone fetal anomalies screening tests between 11 + 0 and 13 + 6 weeks of pregnancy and their PAPP-A and βhCG biomarkers were adjusted to the Multiples of the Median (MOM). MOM PAPP-A <  0.4 and MOM βhCG > 3 were considered abnormal. The samples were followed up until delivery. The biomarkers' levels were compared in the two groups of women with and without PE and Relative risk (RR) and odds ratio (OR) of PE calculated. Results In the PE group, the mean MOM PAPP-A was significantly lower (1 vs. 1.09 with P = 0.006) and MOM βhCG was significantly higher (1.51 vs. 1.14 with P = 0.001) than the group without PE. RR and OR for PE in subjects with MOM PAPP-A <  0.4 were reported as follows: RR = 2.49, (p = 0.001) and OR = 2.09, (p = 0.001). RR and OR for PE in subjects with MOM βhCG > 3 were also reported as follows: RR = 4.02, (p = 0.001) and OR = 5.65, (p = 0.001). Adjusted OR for MOM PAPP-A <  0.4 and MOM βhCG > 3 was obtained as follows: OR = 2.09 (P = 0.001) and OR = 5.65 (P = 0.001), respectively. Conclusion The results of the study showed that the high levels of βhCG would cause 5.65 times increase and the low levels of PAPP-A would cause 2.09 times increase in the chance of developing PE.